Identificação de Enterococcus spp. e avaliação da ocorrência de genes de resistência á vancomicina em amostras de pacientes de hospitais de manaus, AM - Azevedo, Maria Ermelinda Filgueiras de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Enterococcus spp. normally inhabit the gastrointestinal tract of humans and animals. Since 1980, have been identified as a major cause of nosocomial infections. The species E. faecalis and E. faecium are agents of various infections, such as bacteremia, sepsis, endocarditis, urinary tract infections, wound infections and meningitis. Acquired resistance, most predominantly penicillin / ampicillin, aminoglycosides (high-level resistance) and glycopeptides are reported in an increasing number of isolates and therapeutic spectrum in these cases is limited. The main concern is that the genes which encode resistance to these antibiotics could all be transferred to other Enterococci or for many other virulent pathogens. Acquired resistance to glycopeptides is mediated by several mechanisms (types VanA/B/D/E/G/L), with VanA and VanB genotypes are transferable. Factors related to the host, with the hospital, invasive procedures, environment, and the use of antibiotics may increase the risk of colonization or infection with VRE. This study aims to investigate the occurrence of these microorganisms in hospital patients of Manaus - Amazonas, identifying species distribution and antimicrobial resistance profile and vancomycin resistance genes involved. We analyzed 38 Enterococcus spp. from inpatient or outpatient care from October 2011 to September 2012. 29 isolates E. faecalis and 8 E. faecium were confirmed by conventional biochemical tests, the automated methodology and Polymerase Chain Reaction (PCR). An isolate of Enterococcus spp. was identified by automated equipment as E. casseliflavus, identification was not confirmed by PCR. The evaluation of the antimicrobial susceptibility profiles commonly used in clinical practice were performed by disk diffusion methods and automated. There were differences in the results of sensitivity to penicillin and ampicillin between the two methods. There were no isolated ...

Os Enterococcus spp habitam normalmente o trato gastrointestinal de seres humanos e de animais. Desde 1980, foram identificados como importantes agente de infecções hospitalares. As espécies E. faecalis e E. faecium são agentes de diversas infecções, como bacteriemia, sepse, endocardite, infecção do trato urinário, infecções de feridas e meningite. A resistência adquirida, mais predominantemente a penicilina/ampicilina, aminoglicosídeos (alto nível de resistência) e glicopeptídeos são relatados em um número crescente de isolados e o espectro terapêutico nestes casos é limitado. A principal preocupação é que os genes que codificam a resistência para todos esses antibióticos poderiam ser transferidos para outros enterococos ou mesmo para muitos outros patógenos virulentos. A resistência adquirida aos glicopeptídeos é mediada por vários mecanismos (tipos VanA/B/D/E/G/L), sendo que os genótipos VanA e VanB são transferíveis. Fatores relacionados com o hospedeiro, com o hospital, procedimentos invasivos, meio ambiente, e o uso de antibióticos podem aumentar o risco de colonização ou infecção com VRE. Este estudo visa investigar a ocorrência destes microrganismos, em pacientes de hospitais de Manaus - Amazonas, identificando a distribuição das espécies e o perfil de resistência aos antimicrobianos e dos genes de resistência a vancomicina envolvidos. Foram analisados 38 isolados de Enterococcus spp. provenientes de pacientes internados ou de atendimento ambulatorial no período de outubro de 2011 a setembro de 2012. Foram confirmados 29 isolados de E. faecalis e 8 de E. faecium por testes bioquímicos convencionais, pela metodologia automatizada e por Reação da Polimerase em Cadeia (PCR). Um isolado de Enterococcus spp. foi identificado pelo equipamento automatizado como E. casseliflavus, identificação não confirmada pela PCR. A avaliação dos perfis de suscetibilidade aos ...
Keywords: Infeccão hospitalar; Enterococcus; Reação em cadeia de polimerase; Drogas - Resistencia em microorganismos; Infection; Manaus (AM)